Community Participation In Sustainable Environmental Development: Partisipasi Masyarakat Dalam Pembangunan Lingkungan Hidup Yang Berkelanjutan - Rahmawati, Lutfiah; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2023)
This study analyzes community participation in sustainable environmental development in Ketapang Village, Sidoarjo. Descriptive research methods, including observations and interviews, were employed. Primary and secondary data were collected from key informants. The study applied Cohen and Uphoff's theory, identifying four stages of participation. Active community involvement was observed in decision-making processes, while implementation mainly relied on physical labor. Benefit-sharing involved the use of rented commercial facilities. However, community participation in evaluation activities was limited. These findings highlight the need for strategies to enhance inclusive community engagement in sustainable development, leading to positive environmental outcomes. Highlights: Active community involvement: The study reveals significant community participation in decision-making processes, particularly through the Musyawarah Perencanaan Pembangunan Desa (Village Development Planning Meeting), indicating the importance of inclusive community engagement. Limited participation during implementation: The study highlights that community participation during the implementation phase mainly involves physical labor, suggesting the need for strategies to enhance diverse forms of involvement in sustainable development initiatives. Benefit-sharing and facility utilization: Findings show that the community actively participates in benefit-sharing by utilizing rented commercial facilities, emphasizing the importance of ensuring equitable acces s and utilization of resources for sustainable development Keywords: Community Participation, Sustainable Environmental Development, Ketapang Village, Descriptive Research, Cohen and Uphoff's Theory